Cracking in welded steel platform structures during hot-dip galvanization. (September 2017) - DiGiovanni, Christopher; Li, Leijun; Driver, Robert; Callele, Logan
Abstract: Hot-dip galvanizing is a common procedure used to protect structural steels from corrosive environments. However, in a recent construction project involving welded structural steel platforms, numerous connections were found with large cracks in the welded corner joints and T-joints after galvanizing. Historically, in similar projects by the industry partner, cracking did not occur, making this an unforeseen and new phenomenon. The project explored the mechanical properties of the base material, the thermal stresses induced by the hot-dip galvanizing, and the fracture surface of the cracks. A key feature to note is that the fracture surface showed intergranular cracking with no plastic deformation. Lab testing showed the base material exhibited intergranular brittle behavior when heated and fractured at the galvanizing temperature. The transition to a brittle fracture mode is due to temper embrittlement and the segregation of elements in the grain boundaries. Highlights: Cracking occurred in a steel structure during a hot-dip galvanizing procedure. Inclusions and carbide formations were found in the base materials grain boundaries. Hydrogen embrittlement susceptibility was investigated and tested but eliminated as a cause of cracking. FEA was used to the model the galvanizing process and collect metrics on the stresses and temperatures. High phosphorus levels and temper embrittlement testing were found to be the cause of cracking.